Kacciyappa Civācāriya Cuvāmikal aruḷicceyta Kanta purāṇam - Ceṅkalvarāya Piḷḷai, Va. Cu., 1883-1971 (SAMP early 20th-century Indian books project ;, 1952)
Commentary on Kantapurāṇam, verse work in praise of Murugan, Hindu deity, by Kacciyappa Civācāriyar, 12th century Tamil poet.